Self-reported data validity for assessment of systemic and oral health as risk for dependency in old age: a cohort profile of elderly individuals in mid Sweden - Neves-Guimaraes, Alessandra; Udumyan, Ruzan; Jayaprakash Demirel, Kartheyaene; Larsson Gran, Pernilla; Starkhammar, Carin; Källestål, Carina (Frontiers in Oral Health, 2025)
PurposeThe Mid Sweden Cohort (MSC) was established to investigate self-perceived oral and general health among two groups of aging individuals in two counties (Örebro and Östergötland) in Sweden. For internal and external data validation, we linked collected data on health status, behavior, sociodemographic circumstances, and dependency with national register data from Statistics Sweden and compared non-respondents and those lost to follow-up to respondents.ParticipantsMSC is based on a longitudinal multiwave study of aging men and women who answered a cross-sectional questionnaire from MSC: (1) the 1992 cohort including participants aged 50 years in 1992 and (2) the 2007 cohort including participants aged 75 years in 2007. After the baseline surveys, data collection was conducted every 5 years, with the latest wave from 2017 included in our validation. Between 1992 and 2017, 8,879 participants were included in cohort 1, while 5,191 individuals were included in cohort 2 between 2007 and 2017.ResultsAfter linking self-reported data with national register-based data and analyzing loss to follow-up and non-response numbers, we found that, besides age, factors such as being male, having immigrant status, lower income and education level, being single, and being in poor health were predictors of non-response and loss to follow-up, aligning with the findings of other studies. Based on our results, we conclude the MSC is reliable for further research, provided the observed bias is taken into account.Future plansUsing the MSC, we aim to analyze self-reported oral health changes as a predictor of dependency in the elderly and track oral health status over time. Furthermore, we plan to link data with register-based clinical oral health records. We also intend to add the 2022 wave data and future waves into the existing dataset.